On the nature of shape‐fixing in semicrystalline shape‐memory networks. Issue 5 (23rd September 2020) - Yang, Jeh‐Chang; Anthamatten, Mitchell
Abstract: Crystallization of polymer strands within elastically strained cross‐linked networks can lower tension, leading to stabilization of mechanically deformed states. This process, referred to as shape‐fixing, is sensitive to thermomechanical path because both mechanical strain and thermal undercooling affect crystallization kinetics. In the present study, shape‐fixing of a well‐defined poly(caprolactone) network is examined at fixed strains ranging from 25 to 100%. Isothermal crystallization kinetics were studied using wide angle X‐ray scattering while simultaneously monitoring tension loss. Plots of tensile stress versus degree of crystallization show that significant stress reduction occurs at only a few percent crystallinity (<0.05). The development of Young's modulus under identical conditions was evaluated, and results are combined to estimate the shape‐fixity at different crystallization conditions and times. This study contributes to understanding the interrelationship between crystallization, stress reduction, and material stiffening to support further development of semicrystalline shape‐memory networks. Abstract : Crystallization within elastically strained polymer networks can lower tension, retaining macroscopic deformation. This shape‐fixing process depends on the thermomechanical path and is studied at fixed strains of 25–100% using concurrent X‐ray and mechanical stress measurements. Experiments show significantly larger stress reduction at only a few percent crystallization than is predicted by classical theory. Results are related to the shape‐fixing and elastic energy storage ability of these materials.